The relationship between internal and external loads as a tool to monitor physical fitness status of team sport athletes: a systematic review - Adriano Lima-Alves; João Claudino; Daniel Boullosa; Crislaine Rangel Couto; Francisco Teixeira-Coelho; Eduardo M. Pimenta (Termedia Publishing House, 2021)
The efficiency index (Effindex) combines internal and external loads, and it has been considered a promising tool to evaluate physical fitness status. However, its real applicability and limitations have not been elucidated yet. To examine and discuss the findings from studies that used Effindex as a tool for the evaluation of physical fitness status in team sports. A systematic search was performed using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). The databases conferred were PubMed, Scopus, Web of Science, SPORTDiscus, MEDLINE and CINAHL. The articles selected were published up to March 2021. Fourteen articles were included after meeting the inclusion criteria. A wide variety of combinations of external and internal loading parameters to calculate Effindex were found. The pooled sample included 349  male participants (23 ± 3years). Fifty-nine percent of the sample were soccer players, 20% rugby players, 10% Australian football players, 7% hurling players, and 4% basketball players. Most Effindex calculations used total distance (TD) divided by heart rate derived parameters. However, recent studies have suggested the use of accelerations as the external load parameter. Effindex is a simple and powerful tool for the evaluation of physical fitness status in team sports athletes. The disparity of external and internal loading parameters used to calculate Effindex may affect its sensitivity to detect changes in fitness status in different team sport settings. More studies with indoor team sports and female athletes are warranted.